Optimalisasi Pengetahuan Kader tentang Pencegahan Penularan Penyakit Tuberkolusis di Posyandu Bangau Bekasi Barat - Ayu Anggraeni Dyah Purbasari; Afif Amir Amrullah (Lembaga Pengembangan Kinerja Dosen, 2025)
Integrated Health Service Posts (Posyandu) are a means for active community participation in the health sector. Through Posyandu, the role of cadres as the spearhead of environmental health is crucial, especially in educating the community regarding prevention efforts and early detection of various infectious diseases such as tuberculosis (TB). Bekasi City is experiencing an increase in TB cases, so it is necessary to strengthen the capacity of Posyandu cadres to be more responsive and empowered in dealing with this situation. This community service program aims to improve the knowledge and skills of Posyandu cadres in early detection and prevention of TB. The activity was carried out at Posyandu Bangau, West Bekasi, involving 22 active cadres. The implementation method used a participatory and interactive approach, through health education that emphasized the identification of TB symptoms, transmission methods, and community-based prevention strategies. Evaluations were conducted before and after the education to measure the effectiveness of the activity. The evaluation results showed an 80% increase in cadre knowledge after attending the education. This achievement demonstrates that the delivery of accurate and communicative information is very effective in increasing Posyandu cadre awareness. Capacity building for cadres is not only crucial as an initial step in TB prevention, but also as a sustainable effort to build collective community awareness. With the active involvement of cadres and support from health workers, TB risk detection and prevention can be carried out more optimally and comprehensively.